2012
DOI: 10.1371/journal.pone.0037555
|View full text |Cite|
|
Sign up to set email alerts
|

Intranasal “painless” Human Nerve Growth Factors Slows Amyloid Neurodegeneration and Prevents Memory Deficits in App X PS1 Mice

Abstract: Nerve Growth Factor (NGF) is being considered as a therapeutic candidate for Alzheimer's disease (AD) treatment but the clinical application is hindered by its potent pro-nociceptive activity. Thus, to reduce systemic exposure that would induce pain, in recent clinical studies NGF was administered through an invasive intracerebral gene-therapy approach. Our group demonstrated the feasibility of a non-invasive intranasal delivery of NGF in a mouse model of neurodegeneration. NGF therapeutic window could be furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 73 publications
2
57
0
Order By: Relevance
“…Furthermore, AD mice receiving intranasal administrations of IGF-1 [64], insulin [8], NGF [65] or S14G-Humanin [66] exhibit substantially improved cognitive function. In addition, we previously demonstrated that the intranasal administration of SHED-CM reduced the neurological deficits in a rat model of focal cerebral ischemia [34].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AD mice receiving intranasal administrations of IGF-1 [64], insulin [8], NGF [65] or S14G-Humanin [66] exhibit substantially improved cognitive function. In addition, we previously demonstrated that the intranasal administration of SHED-CM reduced the neurological deficits in a rat model of focal cerebral ischemia [34].…”
Section: Discussionmentioning
confidence: 99%
“…Peptides, proteins, trophic factors Insulin [17] Alzheimer's disease [37][38][39][40] Psychosocial stress [41] IGF-1 [7] Huntington's disease [176] Hypoxic Ischemia [177,178] LPS-induced brain injury [179] b-IFN [8,18] --BDNF [19] Ischemia [67] GDNF [12] Parkinson's disease [30] NGF [20,21] Alzheimer's disease [76,77] TBI [78][79][80] Ischemia [81,82] Oxytocin --Aggression [53] Autism [47][48][49]58,180] Self-perception [50] Stress [52] Schizophrenia [55][56][57] Alcohol withdrawal [54] NAP [25] Alzheimer's disease [25,84,85] Mild cognitive impairment [86] Hypobaric hypoxia [87] Osteopontin [23,24] Ischemic stroke [23] Hemorrhagic stroke [24] Orexins [90] Narcolepsy [91][92][93] Olfactory dysfunction [94] NPY...…”
Section: Class Of Agentmentioning
confidence: 99%
“…Intranasal NGF has been most heavily investigated as a therapeutic strategy for mild cognitive impairment and Alzheimer's disease. For instance, intranasal NGF completely rescued memory impairment in mouse models of Alzheimer's disease [76,77], increased the number of choline acetyltransferase-positive neurons, and decreased phospho-tau-positive neurons, b-amyloid-positive neurites and plaque load [77].…”
Section: Fibroblast Growth Factormentioning
confidence: 99%
“…Similarly, Conner et al (2009) found that septal NGF was required for hippocampal LTP and LTM. Interestingly, cholinergic cells are highly susceptible to Alzheimer's disease (AD) pathology (Auld et al 2002;Mesulam 2004), and NGF has been used as a successful therapy in aged rodents and an AD model (Fischer et al 1987(Fischer et al , 1991Backman et al 1996;Frick et al 1997;Capsoni et al 2012). NGF effects in young adult rodents is conflicting (Van der Zee et al 1995;Backman et al 1996;Muller et al 2012), indicating that the therapeutic effects of NGF may only be exerted in impaired states (Fischer et al 1991;Janis et al 1995;Backman et al 1996) and may actually impair memory in the absence of pathology (Backman et al 1996).…”
Section: Spatial Regulation Of Gf Signaling During Plasticitymentioning
confidence: 99%